STIMULUS-ORGANISM-RESPONSE FACTORS DRIVING IMPULSE BUYING IN LIVE-STREAM SHOPPING ENVIRONMENTS: A SYSTEMATIC REVIEW - Muhammad Rezaldi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study reviews empirical research examining what triggers impulse buying in live-streaming commerce and how these triggers work through psychological processes. The review took a systematic approach, using Scopus and DOAJ as the main databases. The search yielded 249 results, of which 34 studies published between 2020 and 2025 were included after screening. The analysis applies the stimulus-organism-response (SOR) framework. Four main types of stimuli appear consistently across studies. Social stimuli include streamer influence, viewer interaction, and social proof. Platform stimuli stem from real-time features that enhance the user experience. Promotional stimuli include time pressure, flash deals, and limited stock displays. Product presentation stimuli include demonstrations and clear visuals that help viewers imagine using the product. These stimuli affect emotional, cognitive, and immersive states. The most common internal responses linked to impulse buying are excitement, trust, perceived value, and flow. The impact of these stimuli varies depending on consumer traits, platform design, and product type. However, most studies rely on cross-sectional surveys from Asian markets, which limits generalization. This review offers an updated model connecting external triggers with psychological mechanisms.